Vibrational frequencies of entrance and exit channels of CH4 with the radical Cl atom in the van der Waals region - Sulaiman, Media Ismael (Sulaimani Journal for Pure and Applied Sciences, 2023)
Vibrational frequencies in the C-H stretching region, equilibrium structures, and the minimum energy of entrance and exit channels of radical chlorine attached to the methane molecule via van der Waals bonds are predicted via ab initio calculations. MP2 theory at the AUG-cc-pVDZ basis set is used for the calculations. Two equilibrium structures at minimum energies are predicted. A radical Cl atom attached by van der Waals bonds to a specific H atom in the CH 4 molecules in one structure. This structure has two bands of C-H vibration frequencies at 3212 cm-1 and 3222 cm -1 that are higher than the C-H vibration of pure CH4. In the second structure at the entrance channel, the chlorine atom connects to a face (tetrahedron) of CH4 by a van der Waals bond that has a deeper minimum of energy than the first structure. The rear structure has two C-H stretches of 3197 cm -1 and 3199 cm -1 . Finally, the minimum energy is predicted for both the first and second structures in the entrance channel, with relative energies of - 2.2 kJ mol-1 and -4.6 kJ mol-1 , respectively. The structure of the exit channel shows a relative minimum energy of 25.7 kJ mol-1 . Our results of the IR spectrum of harmonic vibrational frequencies are original.
Keywords: Vibrational frequency; IR spectra; Van der Waals region; minimum energy